PERAN NEGARA DALAM SUBSIDI KEPADA MASYARAKAT DALAM PEMIKIRAN MUHAMMAD ASAD - Idzam Fautanu (FISIP UIN SGD Bandung, 2018)
This article examines on how Asad elaborates the Islamic texts into a plan of empowering society. This effort bears Islamic thought on modern Islamic order of society. Asad’s analysis of the Qur’an and Sunnah spreads in Islamic world, for his idea was translated into many languages. Using mostly Western literatures at the issue the writer analyses this Asad’s thought and relates it to our problematic time. Finally, this writing shows how dynamic Asad was in the appreciation of Islam and its roles in empowering society.